Resveratrol—Potential Antibacterial Agent against Foodborne Pathogens - Ma, Dexter S. L.; Tan, Loh Teng-Hern; Chan, Kok-Gan; Yap, Wei Hsum; Pusparajah, Priyia; Chuah, Lay-Hong; Ming, Long Chiau; Khan, Tahir Mehmood; Lee, Learn-Han; Goh, Bey-Hing (Frontiers in Pharmacology, 2018)
Foodborne pathogens have caused enormous impact in food safety due to the health risk resulted from consumption of food contaminated with pathogenic microorganisms. The excessive use of antibiotics lead to the decrease in their effectiveness and the resulting emergence of pathogenic resistant strains. This encourages the search for alternatives that are less likely to cause antimicrobial resistance. Natural plant antimicrobials are one of the candidates being researched for their antimicrobial effectiveness given that plants derived products had been used as traditional medicines and they are also generally well accepted by the consumers. Resveratrol (3,5,4’-trihydroxystilbene) is a naturally occurring stilbenoid which has been gaining considerable attention in medical field due to its diverse biological activities. Resveratrol has been reported to exhibit antioxidant, cardioprotective, anti-diabetic, anticancer and antiaging properties. Given that resveratrol is synthesized as a phytoalexin by plants to protect infections from phytopathogens, resveratrol has been investigated for antimicrobial activities in many previous studies to be alternatives to antibiotics. Thus, the purpose of this review is to provide an overview of the published data on the antibacterial activity of resveratrol against foodborne pathogens together with its possible applications in or on foods and also to describe its possible mode of actions. Furthermore, the current knowledge on its potential synergism and future research or applications are also presented and discussed.